Ekphrasis, imagination and persuasion in ancient rhetorical theory and practice - Webb, Ruth, 1963- (Ashgate, 2009)
This is a study of ekphrasis, the art of making listeners and readers 'see' in their imagination through words alone, as taught in ancient rhetorical schools and as used by Greek writers of the Imperial period (2nd-6th centuries CE). The author places the practice of ekphrasis within its cultural context, emphasising the importance of the visual imagination in ancient responses to rhetoric, poetry and historiography. By linking the theoretical writings on ekphrasis with ancient theories of imagination and emotion and language, she brings out the persuasive and emotive function of vivid languag.